Participation, challenges and needs in children with down syndrome during cancer treatment at hospital: a qualitative study of parents' experiences - Bohnstedt, Cathrine; Stenmarker, Margaretha; Olersbacken, Linn; Schmidt, Lone; Larsen, Hanne B.; Schmiegelow, Kjeld; Hansson, Helena (Frontiers in Rehabilitation Sciences, 2023)
Background Studies report that it can be challenging to assess and treat side-effects and symptoms among children who have impairments and difficulties in expressing their needs. Children with Down syndrome have an increased vulnerability and an increased risk for leukaemia. There is sparse knowledge about the parental experience of how treatment and side-effects affect children with Down syndrome with leukaemia, as well as the role of participation during treatment. Purpose This study aimed to explore the perceptions of parents of children with Down syndrome and leukaemia and their perceptions regarding their child’s treatment, side effects and participation during hospital care. Methods A qualitative study design was used, and interviews were conducted with a semi-structured interview-guide. Fourteen parents of 10 children with Down syndrome and leukaemia from Sweden and Denmark, 1-18 years of age, participated. All children had completed therapy or had a few months left before the end of treatment. Data was analysed according to qualitative content analysis. Results Four sub-themes were identified: (1) Continuously dealing with the child’s potential susceptibility; (2) Confidence and worries regarding decisions related to treatment regulation; (3) Challenges in communication, interpretation, and participation; and (4) Facilitating participation by adapting to the child’s behavioural and cognitive needs. The sub-themes were bound together in an overarching theme, which expressed the core perception “Being the child’s spokesperson to facilitate the child’s participation during treatment”. The parents expressed this role as self-evident to facilitate communication regarding the needs of the child, but also regarding how the cytotoxic treatment affected the vulnerable child. Parents conveyed the struggle to ensure the child´s right to receive optimal treatment. Conclusion The study results highlight parental challenges regarding childhood disabilities and severe health conditions, as well as communication and ethical aspects regarding to act in the best interests of the child. Parents played a vital role in interpreting their child with Down syndrome. Involving parents during treatment enables a more accurate interpretation of symptoms and eases communication and participation. Still, the results raise questions regarding issues related to building trust in healthcare professionals in a context where medical, psychosocial and ethical dilemmas are present.